Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1080/00103620701826829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cement Dust on Soil Chemical Properties in the Calabar Environment, Southeastern Nigeria

Abstract: Some chemical properties of soils around the Calabar Cement Company operational area were studied from three profile pits sited at the crest, upper slope, and middle slope topographic positions. The results showed that the soil pH was moderately to slightly acid (mean 5.8), organic-matter content was moderate (mean 2.54%), total N (N) content was low (mean 0.04%), and available phosphorus (P) was high (mean 87.43 mg/kg). Exchangeable calcium (Ca) content was moderate to high (3.02 to 7.44 cmol/kg) in the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 8 publications
3
11
1
Order By: Relevance
“…Generally, tropical soils usually have low nitrogen [24]. This agrees with Ibanga et al [25] who stated in Calabar that a mean value of 0.4 g/kg total nitrogen is low in Calabar environment.…”
Section: Total Nitrogensupporting
confidence: 76%
“…Generally, tropical soils usually have low nitrogen [24]. This agrees with Ibanga et al [25] who stated in Calabar that a mean value of 0.4 g/kg total nitrogen is low in Calabar environment.…”
Section: Total Nitrogensupporting
confidence: 76%
“…Emissions from cement industry activities are known to provide a large contribution of particulate matter (PM) to the atmosphere and to the surrounding soils via both wet and dry deposition (Al-Khashman and Shawabkeh 2006). Despite the global importance of cement plants, there are few published studies regarding the extent of pollution caused by this industry (Al-Omran and Maghraby 2011; Saralabai and Vivekanadau 1995;Zerrouqi et al 2008;Al-Khashman and Shawabkeh 2006;Ibanga et al 2008;Bermudez et al 2010); datasets on environmental levels and the associated health risks of the cement industry are very scarce (Schuhmacher et al 2004(Schuhmacher et al , 2009. A previous study on soil samples near a cement factory in southern Jordan reported that the highest concentrations of Pb, Zn, and Cd were measured in the soil that was closest to the cement factory (Al-Khashman and Shawabkeh 2006); the same elements were affected by cement plant activities in Córdoba City, Argentina (Bermudez et al 2010) and in Saudi Arabia (Al-Omran and Maghraby 2011).…”
Section: Introductionmentioning
confidence: 98%
“…The humidity is highest in August with mean daily relative humidity is 71% in morning and 52 % in the evening 7 . It is located between latitude 27 To study the effect of cement dust, whole area around three cement plants namely; Sarvottam cement plant located at Chakara village (Nokha); Tiger cement plant and Nokha cement plant located in RIICO industrial area at a distance 500 m from each other, whole area around the plants was divided into four radiant directions of east, south, west and north in clockwise manner 8,9 . Soil sample were taken at surface and 15 cm depth at 100m, 500m, 1km, 2km and 3 km distance (10 samples each) in plastic bags of ½ kg each.…”
Section: Methodsmentioning
confidence: 99%
“…The main objective of this study is to assess the impact of dust given out by the nearby located cement plants on the physiochemical characteristic of the soil in their vicinity 5,6 . Further to check whether dust emitted from them has some compound effect on the soil in any direction.…”
Section: Oriental Journal Of Chemistrymentioning
confidence: 99%